Effects on heat-exposed teeth in relation to forensic identification — a pilot study - Shivananda S; Vidya G Doddawad; Aiswarya Anand; Karthikeya Patil; Vidya CS; Suresh J (Egyptian Journal of Forensic Sciences)
Abstract Background Understanding dental alterations at different temperatures is crucial in forensic odontology. Analyzing the effects of extreme heat on teeth provides critical information for victim identification in fire investigations. This study explores structural changes in dental tissues under varying thermal conditions. To analyze and document the changes in teeth subjected to various heat treatments using forensic imaging techniques, and to determine the applicability of these changes in forensic dental investigations. The study involved 24 freshly extracted healthy permanent teeth (12 anterior and 12 posterior), exposed to temperatures of 200 °C, 400 °C, 600 °C, and 800 °C for 15 min using a muffle furnace. Both pre- and post-heat teeth underwent macroscopic and radiographic examinations at various settings. Qualitative changes in dentition were analyzed and calculated as percentages. Results There were no significant radiographic changes in teeth at 200 °C and 400 °C, but a noticeable reduction in radiopacity was revealed in enamel only at 600 °C and in both enamel and dentin at 800 °C at the 80 kV, 11 mA radiographic exposure settings. Conclusion The study found notable radiopacity changes in enamel and dentin above 600 °C. Radiographic analysis of burnt dental remains has potential for improving victim identification and advancing forensic odontology.